Kombinasi penggunaan quadhelix dan tanggul gigitan posterior pada perawatan crossbite anterior - Rhabiah El Fithriyah (Faculty of Dentistry, Universitas Gadjah Mada, 2016)
Combination quad helix and bite riser posterior for anterior crossbite treatment. Anterior crossbite treatment can be done with the appliances either by removable appliances or fixed appliances. One fixed appliance that can be used in the treatment of anterior crossbite is a quad helix with a combination of bite raiser posterior. It is the preferred appliance for correction of maxillary dental constriction in a preadolescent child. Quad helix is activated by widening the anterior or posterior helices. An 11-year-old female patient referred to the clinic with a problem of crowding teeth that affected her appearance. The diagnosis for her case was malocclusions dentoalveolar class I angle along with anterior crossbite 12 and 21, anterior crowding maxilla with convex face profile, shifted median line, and no TMJ disorder. The treatment plan used a quad helix and bite riser posterior followed by a fixed orthodontic treatment. The aim of this study was to correct the anterior crossbite using a combination of a quad helix and bite raiser posterior. The patient was treated using composite bite raiser posterior on the occlusal surface of 16.26, and quad helix soldered to bands and cemented on 16 and 26. The patient was instructed to get her teeth controlled every two week to activate quad helix. After 3 months of active treatment, anterior crossbite was corrected. The appliance was left passively in place for 3 months as retention. The study concluded that crossbite treatment with a combination of a quad helix and bite riser was effective in correcting anterior crossbite in adolescents.ABSTRAKPerawatan crossbite anterior dapat dilakukan dengan beberapa macam alat baik dengan alat lepasan ataupun alat cekat. Salah satu alat semi cekat yang dapat digunakan pada perawatan crossbite anterior adalah quad helix dengan kombinasi tanggul gigitan posterior. Quad helix merupakan alat yang dapat digunakan untuk konstriksi dental di maksila pada masa remaja. Seorang pasien anak perempuan berusia 11 tahun mengeluhkan keadaan giginya yang berjejal dan menganggu penampilannya. Diagnosis kasus adalah maloklusi dentoalveolar kelas I angle disertai crossbite gigi 12 dan 21, crowding anterior rahang atas dengan profil muka cembung, garis median tidak sesuai dan tidak disertai gangguan TMJ. Rencana perawatan menggunakan quad helix dan tanggul gigitan posterior kemudian dilanjutkan dengan perawatan ortodontik cekat. Tujuan artikel ini adalah menyajikan perawatan crossbite anterior dengan menggunakan kombinasi quad helix dan tanggul gigitan posterior. Pasien dirawat menggunakan tanggul gigitan komposit posterior pada permukaan oklusal gigi 16, 26 dan quad helix yang disolder pada molar band dan disementasi di molar band pada gigi 16 dan 26 kemudian pasien diinstruksikan untuk kontrol setiap dua minggu satu kali kunjungan untuk aktivasi quad helix. Setelah perawatan aktif 3 bulan crossbite anterior telah terkoreksi. Alat ditinggalkan di dalam mulut dalam keadaan pasif selama 3 bulan sebagai retensi. Dapat ditarik kesimpulan bahwa perawatan crossbite dengan kombinasi quad helix dan tanggul gigitan posterior efektif dalam mengoreksi crossbite anterior pada remaja.